Hyperhomocysteinaemia Promotes Doxorubicin-Induced Cardiotoxicity in Mice - Rui Fan; Yao Wang; Jinjin Zhang; Xiangbo An; Shuang Liu; Jie Bai; Jiatian Li; Qiuyue Lin; Yunpeng Xie; Jiawei Liao; Yunlong Xia (MDPI AG, 2023)
Doxorubicin, a widely used chemotherapeutic drug in clinical oncology, causes a series of cardiac side effects referred to as doxorubicin-induced cardiotoxicity. Hyperhomocysteinaemia is an independent risk factor for multiple cardiovascular diseases. However, whether hyperhomocysteinaemia contributes to doxorubicin-induced cardiotoxicity is currently unknown. In this study, we explored the pathogenic effects of hyperhomocysteinaemia induced by dietary methionine supplementation (2% wt/wt in rodent chow) in a mouse model of doxorubicin-induced cardiotoxicity. Our data showed that methionine supplementation doubled serum homocysteine levels, inducing mild hyperhomocysteinaemia. Doxorubicin at a cumulative dosage of 25 mg/kg body weight led to significant weight loss and severe cardiac dysfunction, which were further exacerbated by methionine-induced mild hyperhomocysteinaemia. Doxorubicin-induced cardiac atrophy, cytoplasmic vacuolisation, myofibrillar disarray and loss, as well as cardiac fibrosis, were also exacerbated by methionine-induced mild hyperhomocysteinaemia. Additional folic acid supplementation (0.006% wt/wt) prevented methionine-induced hyperhomocysteinaemia and inhibited hyperhomocysteinaemia-aggravated cardiac dysfunction and cardiomyopathy. In particular, hyperhomocysteinaemia increased both serum and cardiac oxidative stress, which could all be inhibited by folic acid supplementation. Therefore, we demonstrated for the first time that hyperhomocysteinaemia could exacerbate doxorubicin-induced cardiotoxicity in mice, and the pathogenic effects of hyperhomocysteinaemia might at least partially correlate with increased oxidative stress and could be prevented by folic acid supplementation. Our study provides preliminary experimental evidence for the assessment of hyperhomocysteinaemia as a potential risk factor for chemotherapy-induced cardiotoxicity in cancer patients.